2020
DOI: 10.1136/gutjnl-2020-322572
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and risk of incident diabetes mellitus: an updated meta-analysis of 501 022 adult individuals

Abstract: ObjectiveFollow-up studies have shown that non-alcoholic fatty liver disease (NAFLD) is associated with an increased risk of incident diabetes, but currently, it is uncertain whether this risk changes with increasing severity of NAFLD. We performed a meta-analysis of relevant studies to quantify the magnitude of the association between NAFLD and risk of incident diabetes.DesignWe systematically searched PubMed, Scopus and Web of Science databases from January 2000 to June 2020 using predefined keywords to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
241
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(261 citation statements)
references
References 42 publications
(66 reference statements)
10
241
1
9
Order By: Relevance
“…Indeed, most of the eligible RCTs have a small sample size (most RCTs included nearly 25-30 individuals for each arm of treatment) and a relatively short period of treatment (i.e., a median period of 26 weeks with only two RCTs with a treatment duration of 48 weeks or more). Most importantly, to date, there are only two RCTs testing the effects of once-daily subcutaneous treatment with liraglutide or semaglutide on resolution of NASH and/or improvement in liver fibrosis stage, which are the two histological features of NAFLD most strongly associated with risk of adverse liver-related and extra-hepatic outcomes in people with NAFLD [10,[42][43][44]. Conversely, there is now a large body of evidence showing that treatment with liraglutide or other long-acting GLP-1 RAs exerts beneficial effects on cardiovascular, mortality, and kidney outcomes in people with T2DM [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most of the eligible RCTs have a small sample size (most RCTs included nearly 25-30 individuals for each arm of treatment) and a relatively short period of treatment (i.e., a median period of 26 weeks with only two RCTs with a treatment duration of 48 weeks or more). Most importantly, to date, there are only two RCTs testing the effects of once-daily subcutaneous treatment with liraglutide or semaglutide on resolution of NASH and/or improvement in liver fibrosis stage, which are the two histological features of NAFLD most strongly associated with risk of adverse liver-related and extra-hepatic outcomes in people with NAFLD [10,[42][43][44]. Conversely, there is now a large body of evidence showing that treatment with liraglutide or other long-acting GLP-1 RAs exerts beneficial effects on cardiovascular, mortality, and kidney outcomes in people with T2DM [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Mantovani et al examined over 122,000 patients with a NAFLD prevalence of 28% and almost 34,000 cases of incident CKD with stage 3 or higher monitored for a mean follow-up of 9 years. The authors found a risk of CKD in NAFLD 1.43 times higher, regardless of risk factors such as age, sex, obesity, hypertension, diabetes [ 228 ].…”
Section: Clinical Impactmentioning
confidence: 99%
“…As mentioned above, on the basis of the common association of both conditions, patients with NAFLD should be screened for T2D [100]. Additionally, given that NAFLD is a definite risk factor for incident T2D [159], a preventive approach is justified in these patients [160]. Importantly, significant liver fibrosis is an independent risk factor for T2D appearance with a hazard ratio of 2.95 (95% CI 1.19-7.31) [161].…”
Section: Type 2 Diabetesmentioning
confidence: 99%